2014
DOI: 10.1177/0022002714535251
|View full text |Cite
|
Sign up to set email alerts
|

Terrorism and the Labor Force

Abstract: Recent studies have identified correlational associations linking terrorism and females' standing in the labor market. Theories have been proposed to explain these associations. Some concluded that women's participation in the labor force could be the driver that moves terrorism; others proposed that terrorism motivates the deviations in the labor force. No study has adequately explored causality and the direction of this association. Using a panel data set of 165 countries and terrorism data from 1980 to 2007… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The data of female labour to total labour were collected from the World Bank's data bank. Many studies on female labour force participation have previously obtained data from the same source (i.e., Berrebi & Ostwald, 2016;Korotayev et al, 2015).…”
Section: Determinants Of Governance and Female Labour: Independent Variablementioning
confidence: 99%
“…The data of female labour to total labour were collected from the World Bank's data bank. Many studies on female labour force participation have previously obtained data from the same source (i.e., Berrebi & Ostwald, 2016;Korotayev et al, 2015).…”
Section: Determinants Of Governance and Female Labour: Independent Variablementioning
confidence: 99%
“…In order to eliminate potential confounding factors that may have affected both the outbreak of an epidemic and the labor force participation rate, we added a set of economic indicators as control variables. Consistent with previous studies on external shocks, we include economic indicators such as GDP per capita, trade openness, and FDI inflow in the regression (Berlemann and Wenzel 2018;Berrebi and Ostwald 2016;Boudreaux, Escaleras, and Skidmore 2019). Wars and disasters other than epidemics may also interfere with labor market outcomes, so we add them as control variables as well.…”
Section: Research Variablesmentioning
confidence: 99%
“…Much of the small but growing body of research on the economic effects of terrorism examines macroeconomic effects (Blomberg, Hess, & Orphanides, 2004;Eckstein & Tsiddon, 2004) and country level outcomes, such as economic growth or income per capita growth (Gaibulloev & Sandler, 2011), foreign direct investment (Abadie & Gardeazabal, 2008;Enders, Sachsida, & Sandler, 2006), trade (Egger & Gassebner, 2015), and labor force participation (Berrebi & Ostwald, 2016). Such studies have been illuminative in highlighting some key concerns, but they may suffer empirically from the possibility that net effects are reflecting "cancelled out" local effects (see Ocal & Yildirim, 2010).…”
Section: Considerationsmentioning
confidence: 99%
“…In smaller countries, the costs of moving across localities or cities could factor in to how much local labor markets are affected. In a country level study on labor market effects of terrorism across 165 countries, Berrebi and Ostwald () found that terrorist attacks discourage female labor force participation and increase the gender gap in labor participation. Based on their robust findings at the country level, there could be similar or more nuanced effects in local economies.…”
Section: Considerationsmentioning
confidence: 99%